Effects of nonsurgical periodontal therapy on high-sensitivity serum c-reactive protein and ESR among Malaysian population with chronic periodontitis - Kamil, Wisam Alaa; Al-Bayati, Lina; Mohamed Ali, Suhaila (2013)
Objectives: The aim of this study was to assess the outcome of the nonsurgical perio¬dontal treatment in terms of its effect on the hs-CRP and ESR in consecutive subjects diagnosed with chronic periodontitis in order to improve sensitivity and specificity. Methods: 25 systematically healthy subjects diagnosed with chronic periodon¬titis were recruited for the study after obtaining the ethical approval from the ethics committee of the International Islamic University Malaysia. Detailed oral hygiene instruction and standard periodontal therapy were performed. Full clinical periodontal parameters including full mouth plaque scores, bleeding on probing, pocket depth and clinical attachment loss were recorded and re-evaluated 3 months after the treatment completion. Blood samples were collected to determine the high-sensitivity serum C-reactive and the erythrocyte sedimenta¬tion rate at baseline and 3 months after the periodontal treatment. Results: Nonsurgical periodontal therapy resulted in significant reduction in the se¬rum CRP level where the average CRP decreased from 1.8 mg/L at baseline to 1.6 mg/L (p=0.009) after 3 months of periodontal therapy, and the marked improvement in the recorded periodontal parameters were confirmed by the significant decrease in the monitored ESR from 8.3 mm/hr to 5.9 mm/hr (p=0.033). Conclusions: In terms of sensitivity and specificity this study demonstrated that nonsurgical periodontal therapy results in a significant reduction in the serum CRP level and ESR.